A modification to thin-airfoil-section theory, applicable to arbitrary airfoil sections, to account for the effects of thickness on the lift distribution - Graham, David; United States. National Advisory Committee for Aeronautics (Washington, D.C. : National Advisory Committee for Aeronautics, 1951)
The manner in which the effects of thickness on the lift distribution are calculated in NACA Report 833, 1945, has been modified to increase the accuracy of the calculation of the load distribution, due to camber and angle of attack, on airfoil sections of arbitrary camber and thickness. Comparison of theoretical and experimental distributions are presented. The results show that the modification improves the predictions of lift distributions for both angle of attack and camber.
NACA TN No. 2298.
"February 1951."
Includes bibliographical references.
Mode of access: Internet.
Keywords: Lift (Aerodynamics); Aerodynamic load; Angle of attack (Aerodynamics); Camber (Aerofoils); Aerofoils